On the economic impacts of medical treatments: work productivity and functioning - Berndt, Ernst (Estudios de Economía, 2016)
In this essay I provide a wide-ranging overview of recent research linking medical treatments to productivity and ability to function. The studies that examine how do illness and medical treatments affect absenteeism, at-work productivity (“presenteeism”) and ability to function vary in the type of data employed, and in particular, on whether ability to function is measured subjectively (by “asking”) or objectively (by “counting”).